Exploiting crude betel nut (Areca catechu Linn.) extracted solution as a natural reagent with sequential injection spectrophotometry for iron analysis in rice samples - Weerasuk B. (2023)
Exploiting natural reagents derived from plant extracts to develop analytical methods promote green chemistry. Betel nut (Areca catechu Linn.) was utilized as a natural reagent for determination of iron(III) by sequential injection spectrophotometry. This method was based on the reaction of iron(III) with natural reagent as betel nut in acetate buffer at pH 5.5, forming an iron(III)-betel nut complex that showed maximum absorption at 565 nm. A linear calibration graph in the range 0.2–10.0 mg L−1 iron(III) gave a correlation coefficient (r2) of 0.9995. Limit of detection and limit of quantification were 0.06 and 0.20 mg L−1, respectively. Relative standard deviation of the repeatability and reproducibility was less than 5.0%. The proposed method was successfully applied for determination of iron(III) content in rice samples, with recoveries ranging from 83.06 to 99.05%. Results agreed well with those obtained from the FAAS technique at the 95% confidence level.